2003
DOI: 10.1093/oxfordjournals.schbul.a007030
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review and Meta-analysis of Northern Hemisphere Season of Birth Studies in Schizophrenia

Abstract: Based on the epidemiological finding that individuals with schizophrenia tend to be born in winter/spring when compared to the general population, we examined (1) the strength and timing of this effect in Northern Hemisphere sites, and (2) the correlation between the season of birth effect size and latitude. Studies were located via electronic data sources, published citations, and letters to authors. Inclusion criteria were that studies specify the diagnostic criteria used, that studies specify the counts of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
220
2
20

Year Published

2004
2004
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 352 publications
(257 citation statements)
references
References 17 publications
15
220
2
20
Order By: Relevance
“…Consistent with this photoperiod hypothesis (but also with a temperature hypothesis), studies of schizophrenia found no seasonal birth effect at the equator (Parker et al, 2000) and, in the northern hemisphere, a stronger effect with increasing latitude (Davies et al, 2003).…”
Section: A Sunlight Hypothesismentioning
confidence: 57%
“…Consistent with this photoperiod hypothesis (but also with a temperature hypothesis), studies of schizophrenia found no seasonal birth effect at the equator (Parker et al, 2000) and, in the northern hemisphere, a stronger effect with increasing latitude (Davies et al, 2003).…”
Section: A Sunlight Hypothesismentioning
confidence: 57%
“…Maternal immune activation is considered to be an etiological factor in schizophrenia based on epidemiological studies of influenza infection in mothers of schizophrenia patients, and an increased incidence of schizophrenia among winter births [125][126][127] . This has been modelled in rodents by infecting pregnant animals with viruses or by administration of the bacterial endotoxin lipopolysaccharide (LPS).…”
Section: Maternal Immune Activationmentioning
confidence: 99%
“…Season of birth (SOB) has been shown to modify risk for several health outcomes, including a number of neuropsychiatric disorders (Brewerton, Dansky, O'Neil, & Kilpatrick, 2012;Cheng et al, 2013;Davies, Welham, Chant, Torrey, & McGrath, 2003;Disanto et al, 2012;Dome, Kapitany, Ignits, & Rihmer, 2010). In effect, there is evidence indicating that seasonality influences fetal growth and development (Currie & Schwandt, 2013;Flouris, Spiropoulos, Sakellariou, & Koutedakis, 2009;Strand, Barnett, & Tong, 2011;Watson & McDonald, 2007), which bears significance for psychiatric research.…”
Section: Introductionmentioning
confidence: 99%